If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10f + 5 = 0 Reorder the terms: 5 + 10f = 0 Solving 5 + 10f = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 10f = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 10f = 0 + -5 10f = 0 + -5 Combine like terms: 0 + -5 = -5 10f = -5 Divide each side by '10'. f = -0.5 Simplifying f = -0.5
| -3(l+4)-l-3=-4(l+5)+5 | | 0.8x-0.4(60+x)=0.067(60) | | 0.18y+0.03(y+6000)=810 | | (2x+2)=-4 | | 16x^7-x^3-65= | | 3/4÷2= | | 6(2/3-3) | | 14x-2(2x-4)=9x+9 | | 4x^4+12x^7=0 | | X+100=-235 | | 8.3x+5=9.7x-1 | | 121x^2-324= | | -9/-3*2/-5*8 | | x+x-28=152 | | -5/6t=15 | | y=2x^2+12x-39 | | 9a^3-5a^3= | | (x^4-25)(x^2-1)=0 | | 0.05*(x^90)=5 | | 12x+3=18x-3 | | 27w/-12w | | 4(m+4)+8(-12m+11)=m-8+8m+11 | | 8(w-84)=88 | | 81=-9(j+87) | | 5(p-65)=85 | | -7(t-9)+2t=-8+t | | 27-m=8 | | 2x/4-1/4=x/3-7/3 | | 4a-11=9+3a | | 5(-6+1)-4n=-5+2n | | 24=-3(t+-24) | | 2(n-52)-22=2 |